2000
DOI: 10.1021/bi001467p
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Mutagenesis of Interleukin 5 Differentiates Sites for Receptor Recognition and Receptor Activation

Abstract: Multisite mutagenesis of single-chain and monomeric forms of human interleukin 5 (IL-5) was performed to investigate mechanistic features of receptor activation and the possibility of differentiating sites of activation from those for receptor interaction. The normally dimeric human IL-5 contains two domains, each containing a four-helix bundle. IL-5 has previously been re-engineered into the monomeric, one-domain GM1 form by introducing an eight-residue linker between the third and fourth helices. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…We surmise that targeting site I will be important to derive a specific antagonist for IL5R␣, whereas blocking site II offers the opportunity to interfere with IL5 biological activity induced by multisubunit receptor recruitment involving ␤c (see below). This can be seen in the IL5 ligand side, as we previously found that the roles of the receptor-binding epitope on IL5 can be separated into receptor recognition residues such as Arg 91 and receptor activation residues such as Glu 110 (35,36). In this regard, considering their charge complementarity, it would be reasonable to speculate that Arg 91 and Glu 110 of IL5 are more likely to be candidates for binding partners of sites I and II on IL5R␣, respectively.…”
Section: Af17121 Utilizes the Receptor Epitope-mentioning
confidence: 85%
“…We surmise that targeting site I will be important to derive a specific antagonist for IL5R␣, whereas blocking site II offers the opportunity to interfere with IL5 biological activity induced by multisubunit receptor recruitment involving ␤c (see below). This can be seen in the IL5 ligand side, as we previously found that the roles of the receptor-binding epitope on IL5 can be separated into receptor recognition residues such as Arg 91 and receptor activation residues such as Glu 110 (35,36). In this regard, considering their charge complementarity, it would be reasonable to speculate that Arg 91 and Glu 110 of IL5 are more likely to be candidates for binding partners of sites I and II on IL5R␣, respectively.…”
Section: Af17121 Utilizes the Receptor Epitope-mentioning
confidence: 85%
“…5A (14)). Although IL5 is a homodimeric protein, it has been shown that the stoichiometry of IL5⅐IL5R␣ interaction is 1:1 (10, 12), and a Langmuir 1:1 binding model has been used for global fitting analysis of IL5⅐IL5R␣ interaction (33). In this article, we first measured the association rates at flow rates of a range of 10 to 80 l/min to examine the mass transfer effect (Fig.…”
Section: Expression and Antibody Capture Of Sil5r␣ Mutationalmentioning
confidence: 99%
“…In the CD turn of this IL-5 mutant, the only charged residue is Arg 90 . Moreover, variants of IL-5 have been constructed which retain the SLRGG CD turn but replace other residues more important for biological activity, leading to the view 19 that the CD turn is important for driving receptor ␣ subunit recruitment but not receptor activation and that mimicking this region could lead to effective IL-5 antagonists.…”
Section: Introductionmentioning
confidence: 99%